DESKRIPSI LINGKUNGAN AGRIBISNIS PERDESAAN DI KECAMATAN SORONG TIMUR KOTA SORONG - Margareta Evin Arne; Ventje V. Rantung; Jenny Baroleh; Jean Fanny Juanita Timban (Sam Ratulangi University, 2015)
Subdistrict East Sorong is producing areas of agricultural products with the highest commodities compared to other areas in the city of Sorong. Kelurahan Klamana and Klawalu are two areas in the district of East Sorong has run rural agribusiness and is a village that has the largest population who are farmers, especially farmers horticulture. The aim of research to determine the circumstances: 1) agriculture, business or field of business, agribusiness perdesan in District East Sorong Sorong City, and 2) farm in the district of East Sorong. This research was conducted in the Eastern District of Sorong Sorong City began in October to December 2014. This study is using the survey method. Retrieval of data are primary data and secondary data. Data were analyzed using descriptive. Results of the study portrait of the general state of agriculture and business, the business field of agriculture, infrastructure support in the district of East Sorong Sorong. Keywords: horticulture, supporting infrastructure, East Sorong